Selective recovery of lithium ions from acidic medium based on capacitive deionization-enhanced imprinted polymers. (1st November 2022) - Han, Ning; Gao, Ruize; Peng, Haisen; He, Qiongqiong; Miao, Zhenyong; Wan, Keji
Abstract: With the increasing demand for lithium resources, recovering lithium from solid wastes (such as spent lithium batteries, lithium-rich fly ash) has become a new source of lithium. To meet the requirements for lithium recovery from acid leached solution of fly ash and spent lithium batteries, a novel imprinted capacitive deionization electrode (Li + -ICDI) was synthesized by cross-linking with dibenzo-14-crown-4 (DB14C4) as the trapping agent, multi-walled carbon nanotubes (MWCNT) as keleton, and polypyrrole (PPy) as the conducting agent. The adsorption capacity in the presence of electric field was about 6 times higher than that without electric field, up to 2047.71 μmol/g in acidic environments (pH = 2). In the presence of Na +, K +, Mg 2+ and Al 3+, the selectivity factor of Li + -ICDI to Li + was 5.94, 9.16, 42.95 and 73.93, respectively. The experimental data can be well described by the pseudo-second-order model and Langmuir adsorption isotherm model. The adsorption capacity remained at 96.18% after 5 cycles, indicating that the obtained electrode materials had excellent regeneration ability. Through the synergistic effect of electric field-driven rapid ion transport and Li + selective recognition of crown ether, Li + -ICDI achieved excellent separation of Li + ions in acidic medium. Graphical abstract: Image 1 Highlights: An innovative method for recovering lithium ions from acidic medium was proposed. Ion imprinting technology and capacitive deionization technology are combined. The maximum adsorption capacity of the Li  +  -ICDI is up to 2047.71 μmoL/g under pH = 2. The crown ether protonation was effectively overcome under electric field. Li  +  -ICDI have high selectivity for Li + in the preference of Na +, Mg 2+, Al 3+ and K + .